FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT - Melyawati, Melyawati; Suryanto, Suryanto (E-Jurnal Akuntansi TSM, 2024)
The purpose of this study is to obtain empirical evidence regarding the influence of leverage, firm size, ROA, sales growth, audit quality, managerial ownership, institutional ownership, and audit committee on earnings management. The population in this study consists of companies in the consumer cyclicals and consumer non-cyclicals sectors listed on the IDX from 2020-2022. The sample was obtained using purposive sampling method, with 63 companies selected as the sample, resulting in a total of 189 data points after outlier testing. This research uses multiple linear regression model to test hypotheses and to analyse the data. The results of this study indicate that leverage, audit quality, and institutional ownership have a negative influence on earnings management, while firm size has a positive influence on earnings management. However ROA, sales growth, managerial ownership, and audit committee do not have an influence on earnings management.